0
$\begingroup$

My question concerns why $(A-\lambda_1 I)(C_1 v_1 + C_2 v_1^{(1)}) = C_2 v_1$ in the calculations below.

Suppose we have a linear system of differential equations with a constant matrix $A \in \mathbb{R}^{3x3}$. $A$ has two distinct eigenvalues $\lambda_1,\lambda_2$ of which the $\lambda_1$ has algebraic multiplicity $n_j =2$ while $\lambda_2$ has $n_j =1$. The general solution can then be found as

$x(t) = e^{At}x_0 = \sum_{j=1}^{2}\left(\left[ \sum_{k=0}^{n_j-1} (A-\lambda_j I)^k \frac{t^k}{k!} \right] x^{0,j} e^{\lambda_j t}\right)$

Choosing $x_0 = \sum_{j=1}^{2} x^{0,j} = C_1v_1 + C_2v_1^{(1)}+C_3v_2$ we get

$x(t) = e^{\lambda_1 t}(C_1v_1 + C_2v_1^{(1)}) + te^{\lambda_1t}(A-\lambda_1 I)(C_1v_1 + C_2v_1^{(1)}) + C_3 e^{\lambda_2 t} v_2 =\\= e^{\lambda_1 t}(C_1v_1 + C_2v_1^{(1)}) + te^{\lambda_1t}(C_2v_1) + C_3 e^{\lambda_2 t} v_2$

What I don't understand is why $(A-\lambda_1 I)(C_1 v_1 + C_2 v_1^{(1)}) = C_2 v_1$.

$\endgroup$
0
$\begingroup$

This is by the definition of generalised eigenvectors. In your case, $v_1$ is a generalised eigenvector of rank 1 (which is basically the same as an ordinary eigenvector). This means that it obeys the equation \begin{equation} A v_1 = \lambda_1 v_1 \qquad \Rightarrow \qquad (A - \lambda_1 I) v_1 = 0. \end{equation} Generalised eigenvectors form a Jordan chain. In this case, this means that the generalised eigenvector $v_1^{(1)}$, which is of rank 2, obeys the equation \begin{equation} (A - \lambda_1 I)v_1^{(1)} = v_1, \end{equation} such that \begin{equation} (A-\lambda_1 I)^2 v_1^{(1)} = 0. \end{equation}

$\endgroup$
  • $\begingroup$ Thank you @frits-veerman, that makes a lot of sense! $\endgroup$ – langkilde Mar 31 '16 at 12:02

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.